Gender, caste, and class in South India's technical institutions - Hebbar N., Nandini (Oxford: Oxford University Press, 2024)
"The introductory chapter examines how the immense social value placed on technical education as a viable route to a good life, respectable middle-class identity, and high status have contributed to a specific kind of subject-making on engineering campuses across Tamil Nadu. While enforcing a performativity of the acceptable in the social realm, the institutional structure also propagates a pedagogy that is uncritical and mechanically derived; a pedagogy that emphasizes application over criticism, and structure over individual. Though students are not simply 'interpellated' by this pedagogy and disciplinary framework in an Althusserian manner, it does have a role to play in crafting a distinct subjectivity and sense of self-worth. Even as students negotiate these institutional constraints, it has become an integral part of college life and the ways in which 'youth' is experienced"--
Keywords: Education, -- Engineering college